1996
DOI: 10.1507/endocrj.43.53
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Dipeptidyl Peptidase IV (CD26) and Thyroid Peroxidase in Neoplastic Thyroid Tissues.

Abstract: Abstract.This paper reports the results of research to examine the possibility of using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
2
13
1
Order By: Relevance
“…9,16 We have reported that thyroid carcinoma expresses aberrant dipeptidyl peptidase IV (CD26/DPPIV) and that enzymatic and immunohistochemical stainings of CD26/DPPIV are useful for the pathological and cytological diagnosis of thyroid tumors. [17][18][19][20] Our observations on CD26/DPPIV overexpression in thyroid neoplasms have been supported by many researchers. [21][22][23] CD26/DPPIV is a membranebound enzyme that hydrolyzes the N-terminal-end of proline-containing peptides.…”
supporting
confidence: 63%
“…9,16 We have reported that thyroid carcinoma expresses aberrant dipeptidyl peptidase IV (CD26/DPPIV) and that enzymatic and immunohistochemical stainings of CD26/DPPIV are useful for the pathological and cytological diagnosis of thyroid tumors. [17][18][19][20] Our observations on CD26/DPPIV overexpression in thyroid neoplasms have been supported by many researchers. [21][22][23] CD26/DPPIV is a membranebound enzyme that hydrolyzes the N-terminal-end of proline-containing peptides.…”
supporting
confidence: 63%
“…Among them are dipeptidylpeptidase 4 (DPP4; refs. [19][20][21][22], a-1 antitrypsin (SERPINA1; ref. 23), galectin 3 (LGALS3; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Mutated TPO genes were found in some differentiated thyroid carcinomas (Smanik et al, 1994). Although the expression of TPO mRNA was found to be the same in cancerous and benign tissue in one study (Ohta et al, 1991), others have shown suppression of TPO gene expression (Hoang-Vu et al, 1992;Fabbro et al, 1994;Tanaka et al, 1996;Umeki et al, 1996).…”
mentioning
confidence: 97%
“…Some differences in the results of experiments using TPO murine monoclonal antibodies to detect protein expression may be due to methodological approaches (Yamashita et al, 1993;Mizukami et al, 1994;Tanaka et al, 1996;Umeki et al, 1996). However, differential immunohistochemical labelling of TPO with one monoclonal antibody (mAb#47) was proposed by De Micco et al (1991) as a marker distinguishing between benign and malignant thyroid tumours, including both PTC and FTC.…”
mentioning
confidence: 99%